Elevated DNA Damage, Oxidative Stress, and Impaired Response Defense System Inflicted in Patients With Myocardial Infarction - Shahzad, Sumayya (Clin Appl Thromb Hemost, 2017)
BACKGROUND: Ischemic tissue damage in myocardial infarction (MI) is allied with the exaggerated production of reactive oxygen species (ROS) beyond the countering capability of chain-breaking radical scavengers, fallouts in the form of oxidatively burdened myocardial tissue. METHODS: One hundred and twenty five patients with MI were included in the study to evaluate the dynamics of redox status of patients by monitoring the antioxidant potential, biomarkers of oxidative stress, lipid indices, RBC membrane damage when compared to healthy individuals in patients with MI congregated on the basis of Global Registry of Acute Coronary Events (GRACE) score, risk factors, and age. RESULTS: Higher levels of malondialdehyde, 8-hydroxy-2-deoxyguanosine, lipid indices, ROS content, and membrane deterioration in erythrocytes were seen in patients with MI. Furthermore, reduced activities of erythrocyte antioxidant enzymes and lower concentrations of antioxidant molecules, plus reduced total antioxidant capacity, were observed in plasma of all patients with MI with respect to control. However, elevation in oxidative stress was found to be significantly marked in patients having GRACE score >100, risk factors, and MI >45 years when compared to patients with GRACE score ≤100, without risk factors, and MI ≤45 years, respectively. CONCLUSION: These findings indicate the existence of increased oxidative damage and reduced antioxidant potential in patients with MI have a potent relationship with their GRACE risk score, risk factors, and age.